2001
DOI: 10.1128/jcm.39.12.4227-4232.2001
|View full text |Cite
|
Sign up to set email alerts
|

Laribacter hongkongensis gen. nov., sp. nov., a Novel Gram-Negative Bacterium Isolated from a Cirrhotic Patient with Bacteremia and Empyema

Abstract: A bacterium was isolated from the blood and empyema of a cirrhotic patient. The cells were facultatively anaerobic, nonsporulating, gram-negative, seagull shaped or spiral rods. The bacterium grows on sheep blood agar as nonhemolytic, gray colonies 1 mm in diameter after 24 h of incubation at 37°C in ambient air. Growth also occurs on MacConkey agar and at 25 and 42°C but not at 4, 44, and 50°C. The bacterium can grow in 1 or 2% but not 3, 4, or 5% NaCl. No enhancement of growth is observed with 5% CO 2 . The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
126
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(129 citation statements)
references
References 18 publications
3
126
0
Order By: Relevance
“…With the whole genome sequencing data of more than 100 bacteria and archaea available, it has been noted that there are relatively small interoperon heterogeneities for 16S rDNAs. In our experience in 16S rDNA sequencing, both for the known species and novel genera and species, direct sequencing of the PCR products has always been successful (16,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)30). In this study, when we first amplified the 16S rDNA of HKU15 T and sequenced the PCR product directly, it was repeatedly observed that the 5' end of the PCR product could not be sequenced clearly, with the presence of multiple peaks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the whole genome sequencing data of more than 100 bacteria and archaea available, it has been noted that there are relatively small interoperon heterogeneities for 16S rDNAs. In our experience in 16S rDNA sequencing, both for the known species and novel genera and species, direct sequencing of the PCR products has always been successful (16,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)30). In this study, when we first amplified the 16S rDNA of HKU15 T and sequenced the PCR product directly, it was repeatedly observed that the 5' end of the PCR product could not be sequenced clearly, with the presence of multiple peaks.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial DNA extraction was performed according to our previous publications (24,30). Briefly, 80 µl of NaOH (0.05 M) was added to 20 µl of bacterial cells suspended in distilled water and the mixture was incubated at 60 C for 45 min, followed by addition of 6 µl of Tris-HCl (pH 7.0), achieving a final pH of 8.0.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, other genera, e.g. Laribacter (Yuen et al, 2001) and Microvirgula (Patureau et al, 1998), have been described and assigned to the family Neisseriaceae.Organisms within the family Neisseriaceae can be isolated from a range of environmental sources (Moss & Bryant, 1982) as well as from different human and animal mucosal surfaces (Kuhn, 1981;Snell, 1984). Only two species, Neisseria gonorrhoeae and Neisseria meningitidis, are wellestablished human pathogens (Morse & Knapp, 1991).…”
mentioning
confidence: 99%
“…In recent years, other genera, e.g. Laribacter (Yuen et al, 2001) and Microvirgula (Patureau et al, 1998), have been described and assigned to the family Neisseriaceae.…”
mentioning
confidence: 99%
“…For example, protein expression in Gram-negative bacterium Laribacter hongkongensis cultured at 20°C and 37°C were compared using 2-DE . L. hongkongensis is a recently discovered β-Proteobacterium that is associated with community-acquired gasteroenteritis and traveler's diarrhea (Yuen et al, 2001;Woo et al, 2004;Woo et al, 2005). It can inhabit in the intestines of freshwater fish, frogs and humans, and can also grow independently in freshwater environments (Woo et al, 2004;Teng et al, 2005;Lau et al, 2007;Ni et al, 2007;Lau et al, 2009).…”
Section: Differential Proteomicsmentioning
confidence: 99%